1987
DOI: 10.1152/jappl.1987.63.2.540
|View full text |Cite
|
Sign up to set email alerts
|

No gravity-independent gradient of blood flow distribution in dog lung

Abstract: The existence of a major gravity-independent gradient of blood flow in lungs has recently been described based on single photon emission computed tomography after intravenous injection of radioactively labeled macroaggregates. We wanted to test this hypothesis of a major gravity-independent gradient in lung blood flow in experiments with direct measurement of macroaggregate distribution in the dog lung. In six anesthetized (4 prone spontaneously breathing, 2 mechanically ventilated) dogs we injected 111In-labe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
24
2

Year Published

1990
1990
2014
2014

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 0 publications
3
24
2
Order By: Relevance
“…The hilar-peripheral gradient of PBF has also been found previously in a number of studies of adult animals including humans (9), dogs (19), sheep (20) and ponies (21) with contradictory evidence in dogs (22). A radial gradient is consistent with the fractal branching pattern of the pulmonary circulation in which vascular resistances is determined by the size of branching vessels and the length of circuit pathways.…”
Section: Diverse Pulmonary Blood Flow In Pigletssupporting
confidence: 73%
“…The hilar-peripheral gradient of PBF has also been found previously in a number of studies of adult animals including humans (9), dogs (19), sheep (20) and ponies (21) with contradictory evidence in dogs (22). A radial gradient is consistent with the fractal branching pattern of the pulmonary circulation in which vascular resistances is determined by the size of branching vessels and the length of circuit pathways.…”
Section: Diverse Pulmonary Blood Flow In Pigletssupporting
confidence: 73%
“…This large central-peripheral gradient was not confirmed by other investigators, who found either much smaller (Glenny et al 1991;Jarvis et al 1992) or no gradients (Newhouse et al 1968;Hedenstierna, White & Wagner 1979;Beck & Rehder 1986;Nicolaysen et al 1987). It has been suggested that the large gradient observed by Hakim and associates may be caused by an artefact due to the complicated data analysis (Nicolaysen et al 1987;Beck, OConnor & Schroeder 1990). Nevertheless, some central-peripheral gradient may exist, which emphasize the point that factors other than gravity are important in the blood flow distribution (Glenny et al 1991).…”
contrasting
confidence: 59%
“…Beck and Rehder (8) also studied microsphere-injected TLC-dried lungs, but they systematically sampled and mapped small cores from transverse slices of the dried specimen. Nicolaysen et al (45) used circumferentially cut sections from partially inflated and frozen RMS-labeled lungs to refute the existence of a significant radial gradient of flow in the lung. After intravenous injection of a flow label, Glenny and Robertson (25) employed in situ supine tissue fixation and acquired gamma camera images of transverse slices of the fixed lung.…”
Section: Methods To Create Microsphere Maps Of Flowmentioning
confidence: 99%
“…As additional high-resolution studies accumulated over time (8,45), it became clear that some factor unrelated to the gravitational gradient was responsible for a major component of the spatial heterogeneity of regional blood flow. Inspired by a demonstration of scale-dependent heterogeneity of cardiac blood flow (5, 37), a high-resolution study of lung perfusion distribution confirmed that the spatial heterogeneity of regional blood flow increased in a similar predictable fashion as resolution was enhanced (25).…”
Section: Scale-dependent Heterogeneity Of Lung Blood Flowmentioning
confidence: 99%